A fractal concentrator of direct and indirect sunlight. Issue 4 (16th November 2020) - Katardjiev, Ilia
Abstract : A novel concept for concentrating both direct and indirect sunlight is presented. A concentrator designed accordingly is numerically predicted to have transmittance exceeding 90% for incidence angles up to 65 degrees at low concentrations. Abstract: A novel concept for concentrating both direct and indirect sunlight employing a combination of waveguiding and refractive optics is presented. More specifically, it is based on both the individual and the collective focusing effects of an array of refractive optical elements of specific geometry. An analytical framework and design principles regarding the geometry of the optical elements taking into account Fresnel reflection and refraction are presented. The principle of operation along with loss mechanisms and acceptance angles are discussed in detail. Ray-tracing simulations of a light concentrator designed accordingly indicate transmittance >90% with acceptance angles of ≤65° at 3 suns for moderate refractive indices. It is further numerically demonstrated that the new approach allows the utilization of the dominant fraction of the solar radiation by harvesting the waste heat in addition to photovoltaic conversion with an operating energy efficiency for diffuse light >70%. Graphical Abstract: